The effect of Cd2+ ions on the passive permeability of the mitochondrial membrane of liver cell of Rats - Tojikulova Oysora; Asrarov Muzaffar; Bazarov Baxritdin; Rakhmatova Nigora; Turamkulov Shokir; Baratova Shoxsanam (BIO Web of Conferences)
This article describes the results of a study conducted on rats on the effects of heavy metal salts, including Cd2+ ions, on mitochondrial membranes. The experiments showed that heavy metals are one of the most dangerous sources of environmental pollution, and that they have a strong genotoxic, tumor-causing and cytotoxic effect when ingested. Cd2+ poisoning occurs in the metallurgical industry through inhalation of atmospheric air, consumption of contaminated food and water, and cigarette smoke. The studies showed that the studied heavy metal salts, Cd2+ ions, negatively affect the structure of the mitochondrial membrane, increasing the passive permeability of the membrane for monovalent H+, K+ and Na+ cations.